An approach for efficient energy consumption and delay guarantee MAC protocol for wireless sensor networks - Shukur, Marwan Ihsan; Vooi, Voon Yap (2009)
Wireless sensor networks is an emergent technology that open a world of environment controlling, helping the administrator to predict and anticipate for any possible action that the environment could produce.Unfortunately these energy constrained miniatures must operate in a way that keeps fair consuming between sensor nodes to reach efficient network productivity.In this paper we present a MAC protocol that offers an improved energy efficient consumption and efficient delay guarantee operation. Simulation results shows that the proposed scheme provided better operation than S-MAC protocol.